U.S. Companies in Argentina: Trade and Investment Patterns (1890 1930) - Lluch, Andrea Mari (2019)
Argentina was viewed as the least Americanized country in Latin America at the beginning of the twentieth century. However, the role U.S. companies in shaping the Argentinean economy in the first decades of the twentieth century has not yet been fully documented. For this reason, this article provides a new estimate of the scope and characteristics of U.S. interests in Argentina, and try to explain the role and impact of U.S. firms in Argentina's economic growth to 1930. It proposes that the impact of U.S. investments on the Argentinean economy was of longer standing and more widely diversified than has generally been assumed.